Autofluorescence hyperspectral imaging of radiofrequency ablation lesions in porcine cardiac tissue. Issue 8 (22nd August 2016) - Gil, Daniel A.; Swift, Luther M.; Asfour, Huda; Muselimyan, Narine; Mercader, Marco A.; Sarvazyan, Narine A.
Abstract : Radiofrequency ablation (RFA) is a widely used treatment for atrial fibrillation, the most common cardiac arrhythmia. Here, we explore autofluorescence hyperspectral imaging (aHSI) as a method to visualize RFA lesions and interlesional gaps in the highly collagenous left atrium. RFA lesions made on the endocardial surface of freshly excised porcine left atrial tissue were illuminated by UV light (365 nm), and hyperspectral datacubes were acquired over the visible range (420–720 nm). Linear unmixing was used to delineate RFA lesions from surrounding tissue, and lesion diameters derived from unmixed component images were quantitatively compared to gross pathology. RFA caused two consistent changes in the autofluorescence emission profile: a decrease at wavelengths below 490 nm (ascribed to a loss of endogenous NADH) and an increase at wavelengths above 490 nm (ascribed to increased scattering). These spectral changes enabled high resolution, in situ delineation of RFA lesion boundaries without the need for additional staining or exogenous markers. Our results confirm the feasibility of using aHSI to visualize RFA lesions at clinically relevant locations. If integrated into a percutaneous visualization catheter, aHSI would enable widefield optical surgical guidance during RFA procedures and could improve patient outcome by reducing atrial fibrillation recurrence. Abstract : Effective treatment of atrial fibrillation, the most prevalent cardiac arrhythmia, is highly dependent on the correct placement of radiofrequency ablation lesions. However, few options are currently available to guide lesion placement. Autofluorescence hyperspectral imaging relies on subtle changes in the autofluorescence emission spectrum to successfully delineate radiofrequency ablation lesions placed on the endocardial surface of left atrium. Our results support the application of autofluorescence hyperspectral imaging for improved radiofrequency ablation guidance.